2006
DOI: 10.1590/s0100-72032006000700003
|View full text |Cite
|
Sign up to set email alerts
|

Desejo, intenção e comportamento na saúde reprodutiva: a prática da cesárea em cidade do Nordeste do Brasil

Abstract: Desejo, intenção e comportamento na saúde reprodutiva: a prática da cesárea em cidade do Nordeste do BrasilWishes, intention and behavior in reproductive health: the practice of cesarean section in a city in the northeast of Brazil Nilma Dias Leão Costa 1 , Neir Antunes Paes 2 , Paulo César Formiga Ramos 3 , Maria Célia de Carvalho Formiga 4 RESUMO Objetivo: investigar os fatores determinantes da alta incidência do parto cesáreo e a sua inter-relação com a esterilização. Métodos: a pesquisa é parte de estudo m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 6 publications
1
17
0
2
Order By: Relevance
“…In Brazil, considering the total number of children of women of childbearing age, the percentage of children aged 15 to 19 years increased in that total (22) . Pregnancies and age at which TL was done, were positively correlated, that confirms the findings of a study in which women who had fewer children underwent sterilization younger and had higher education (15) . It is interesting to be noticed that women who were sterilized before age 35, have 17 times more probability of repenting.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In Brazil, considering the total number of children of women of childbearing age, the percentage of children aged 15 to 19 years increased in that total (22) . Pregnancies and age at which TL was done, were positively correlated, that confirms the findings of a study in which women who had fewer children underwent sterilization younger and had higher education (15) . It is interesting to be noticed that women who were sterilized before age 35, have 17 times more probability of repenting.…”
Section: Discussionsupporting
confidence: 82%
“…Research carried out in Ribeirão Preto (SP) with 235 sterilized women, as well as in a documentary study with 95 medical records of candidates for TL in the same city, found an average of pregnancies that is similar to the found in this study, that that would provide high efficacy, safety, health, ease-ofuse, acceptable by customs and the sexual partner; the more intense expectation was closely associated with TL (21) . There is a strong association between parity and level of education; the higher association was found among primiparous (81%) women with higher educational level (15) . The less educated the greater the offspring number (17) .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Este evento repercute, inclusive, na dificuldade de se estabelecer associação entre tipo de parto e os desfechos. A escolha pelo parto cirúrgico nem sempre reflete uma indicação clínica, e sim uma prática obstétrica influenciada por questões socioeconômicas, culturais e comportamentais 32 . A partir de pesquisas, nos bancos de dados Medline e LILACS/SciELO, verificamos que o presente trabalho constitui o primeiro estudo prospectivo na Paraíba sobre ganho de peso gestacional, com as características metodológicas aqui utilizadas.…”
Section: Discussionunclassified
“…In search of understanding this phenomenon, recent studies have scrutinized factors associated with cesarean deliveries, such as, type of institution (public or private), geographical region, socioeconomic level of women or characteristics of professionals and medical care. [7][8][9][10][11][12][13] A part of the literature analyzes maternal and perinatal outcomes, comparing cesarean with vaginal deliveries, and demonstrated worse results for the surgery, in terms of morbidity and mortality, mainly among women living in less privileged social and healthconditions. [14][15][16] Some studies used a clinical and/or surgical approach and address the use of medication, evaluation of the pelvic floor, postpartum depression, among other clinical issues.…”
Section: Introductionmentioning
confidence: 99%